AVALIAÇÃO DE SUSTENTABILIDADE URBANA: PROPOSTA PARA UM CONJUNTO MÍNIMO DE INDICADORES - Linguitte, Marcelo; Marins, Karin (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Owing to the relevant impact of the cities on the global sustainable development, many concepts, initiatives, tools and references have been created to support the involvement of cities with the theme of sustainable development. Examples are the ISO 37120, the Emerging Sustainable Cities Program (IDB), the Sustainable Cities Program (Rede Nossa São Paulo and Ethos Institute) and the Global City Indicators (World Bank. All these references propose different visions about what would be a sustainable city and which indicators should be used to monitor the progress towards higher degrees of sustainability of the cities. This paper intends to evaluate the indicators proposed by the main references in urban sustainability and identify those that are most commonly used by the majority of these references to compose the minimum set of indicators to be monitored in the search for a more sustainable city.